2021
DOI: 10.1097/bpo.0000000000001821
|View full text |Cite
|
Sign up to set email alerts
|

When Should Instrumentation to the Pelvis be Considered in Minimally Ambulatory Adolescents With Neuromuscular Scoliosis?

Abstract: Introduction:The goal of neuromuscular scoliosis (NMS) surgery is to improve sitting balance, facilitate daily care, and alleviate pain. In nonambulatory patients, where sitting balance is key, fusion to the pelvis is usually required. However, in minimally ambulatory patients, fusion to the pelvis remains controversial, and there is considerable practice variability in this patient population. The purpose of this study is to evaluate and summarize the available evidence regarding fusion constructs in minimall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…On the one hand, scoliosis straightens better, but the other hand patents have more limited movement freedom, what can lead to a decrease in functional independence and quality of life. There are still heated debates now 19 .Most patients will have spinopelvic xation 1 .The exception is ambulatory patients with NMS with adequate head control, without hip subluxation or dislocation and small degree pelvic obliquity (< 15°), they may not need pelvis xation 20 .…”
Section: Resultsmentioning
confidence: 99%
“…On the one hand, scoliosis straightens better, but the other hand patents have more limited movement freedom, what can lead to a decrease in functional independence and quality of life. There are still heated debates now 19 .Most patients will have spinopelvic xation 1 .The exception is ambulatory patients with NMS with adequate head control, without hip subluxation or dislocation and small degree pelvic obliquity (< 15°), they may not need pelvis xation 20 .…”
Section: Resultsmentioning
confidence: 99%
“…It should be pointed out that the range of spinal correction and fixation in ambulatory patients with syndromic scoliosis remains controversial. [12] Previous studies have revealed that, especially in nonambulatory patients with neuromuscular scoliosis, extending instrumentation to the pelvis improves scoliosis correction and sitting balance if the angle of PO exceeds 10° to 15°. [13][14][15][16] In this case, the patient was ambulatory at the time of surgery; however, the nature of her progressive scoliosis had caused the PO angle to increase significantly.…”
Section: Discussionmentioning
confidence: 99%
“…3 ) [ 33 ]. In a recent review article, fusion short of the pelvis was considered in patients with adequate head control without the presence of hip subluxation or dislocation and when pelvic obliquity is < 15° [ 34 ]. In our opinion, if pelvic obliquity is associated with coronal imbalance, especially C-type neuromuscular scoliosis, pelvic fixation should be performed considering the correction of the curve and postoperative coronal balance.…”
Section: Surgical Techniquementioning
confidence: 99%
“…Although we can do the stable lumbosacral fixation, the selection between the mobility for the advantages in performing transfers, weight shifts, or rotational mobility, and the fusion for the correction of pelvic obliquity for sitting balance is questionable. Douleh et al [ 34 ] suggested adequate head control as a guide for L5–S1 preservation. This indication looks ideal considering proximal junctional problem.…”
Section: Problems In Pedicle Screw Eramentioning
confidence: 99%